Classroom Norms and Individual Smoking Behavior in Middle School - Yarnell, Lisa M. (2012)
OBJECTIVES: To investigate whether smoking prevalence in grade-level networks influences individual smoking, suggesting that peers are important social multipliers in teen smoking. METHODS: We measured gender-specific, grade-level recent and life-time smoking among urban middle-school students who participated in Project Northland Chicago in a longitudinal cohort design. RESULTS: Within schools, grade-level recent smoking had comparable effects on girls’ and boys’ individual-level smoking. Grade-level lifetime smoking had a greater effect on girls’ smoking. CONCLUSION: Interventions can target middle school classes and schools broadly, without making the identification of friendship networks a concern.